2013
DOI: 10.1016/j.tranpol.2013.09.019
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for measuring the sustainability of car transport systems

Abstract: Measuring the sustainability of car fleets, an important task in developing transport policy, can be accomplished with an appropriate set of indicators. We applied the Process Analysis Method of sustainability assessment to generate an indicator set in a systematic and transparent way, that is consistent with a declared definition of a sustainable transport system. Our method identifies stakeholder groups, the full range of impacts across the environmental, economic and human / social domains of sustainability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 33 publications
(33 reference statements)
0
10
0
2
Order By: Relevance
“…A sustainable transport system requires planning, which in turn needs monitoring, evaluation and assessment of the current system, and any proposed changes (Shiau & Liu, 2013). Sustainability assessments of transport systems have been conducted within the fields of transport studies and transport geography by use of various approaches and indicators (Smith, Axon, & Darton, 2013). Among them, accessibility has been a recurring oneeither in combination with other measures (Rubulotta, Ignaccolo, Inturri, & Rofè, 2012;Toth-Szabo & Várhelyi, 2012) or as a sole indicator (Amoroso, Caruso, & Castelluccio, 2012;Kwok & Yeh, 2004).…”
Section: Sustainable Transport Accessibilitymentioning
confidence: 99%
“…A sustainable transport system requires planning, which in turn needs monitoring, evaluation and assessment of the current system, and any proposed changes (Shiau & Liu, 2013). Sustainability assessments of transport systems have been conducted within the fields of transport studies and transport geography by use of various approaches and indicators (Smith, Axon, & Darton, 2013). Among them, accessibility has been a recurring oneeither in combination with other measures (Rubulotta, Ignaccolo, Inturri, & Rofè, 2012;Toth-Szabo & Várhelyi, 2012) or as a sole indicator (Amoroso, Caruso, & Castelluccio, 2012;Kwok & Yeh, 2004).…”
Section: Sustainable Transport Accessibilitymentioning
confidence: 99%
“…From the perspective of health and safety, the greatest number of indicators was identified in the works of Smith et al (2013), Jeon & Amekudzi (2005) and Cheng & Chen (2015), as shown in Figure 17. The most relevant indicators were accidents with fatality, traffic accidents, safety in the use of public transport service, pollution effect health and medical expenses associated with transportation.…”
Section: Metrics and Urban Mobility Performance Indicatorsmentioning
confidence: 99%
“…En [17] se identifican indicadores como el consumo de combustible, la accidentalidad, la calidad del servicio y el mantenimiento de los vehículos; mientras que en [18] se mide la eficiencia de las rutas en función del tiempo de viaje, la distancia entre destinos, el número de paradas realizadas, el consumo de combustible y la velocidad promedio. En cuanto a indicadores asociados al transporte de mercancía en cadenas de suministro específicas, en [19] se analizan los indicadores de competitividad en la cadena de suministro de la comida; incluyendo el número de empleados capacitados, el uso de combustible, el costo total de transporte, el número de ordenes despachadas sin errores y el cumplimiento con los tiempos.…”
Section: Estado Del Arteunclassified
“…Se espera maximizar el valor calculado. (17) 3.8. Retrasos en la Entrega -RE Es la relación entre tiempo real de entrega y la diferencia con el tiempo estimado; se espera que este indicador se minimice en función del nivel de servicio que la empresa desea establecer.…”
Section: Cumplimiento Al Tiempo De Consolidación O Desconsolidación -unclassified